Synthesis of hydrogen tungsten bronzes HxWO3 by reactive mechanical milling of hexagonal WO3 - Castro, Facundo (2010)
Recently we have reported the formation of hydrogen tungsten bronzes by reactive mechanical milling monoclinic tungsten (VI) oxide under hydrogen atmosphere. In this work we report the milling of hexagonal WO3 under H2 atmosphere. Our main results are the structural transformation of the hexagonal oxide to the high temperature polymorph of WO3 with orthorhombic structure, and the formation of different hydrogen tungsten bronzes at distinct milling times. The bronzes seem to be formed from the orthorhombic oxide, and compared with the bronzes obtained by milling monoclinic WO3 are rather unstable after short exposure to air. The materials are characterized by X-ray diffraction (XRD), Differential Scanning Calorimetry (DSC) and total hydrogen content determination.